The IVF blueprint : everything you need to know about in vitro fertilization, egg freezing, and embryo transfer - Eblen, Abby; Bedient, Carrie M.; Hudson, Susan, Dr (Little, Brown Spark, 2025)
The definitive guide to IVF from leading physicians who have helped thousands of patients successfully navigate fertility treatment--and will demystify the process for you. Wherever you are in your fertility journey, you're bound to have questions. What should I ask at the first doctor visit? Are there supplements that might give my ovaries that extra kick? Do I have a good chance of getting pregnant? Drs. Abby Eblen, Carrie Bedient, and Susan Hudson get real about what you can really expect from IVF--and simplify the complex world of fertility to give you the best possible chance of success. The IVF Blueprint covers every aspect of the process, from preparing for IVF to egg retrieval, recovery, embryo transfer, and more, including valuable insights on: The science behind IVF and egg freezing; Step-by-step explanations of each procedure; Strategies to maximize your odds of success; Emotional and physical considerations during treatment. Combining deep expertise, their personal experiences as IVF patients, and the candid style of their Fertility Docs Uncensored podcast, Drs. Abby, Carrie, and Susan are there with you for every step of the way, sharing everything they know to help you welcome your newest family member.